2016
DOI: 10.2196/jmir.5712
|View full text |Cite
|
Sign up to set email alerts
|

mHealth Intervention to Improve Diabetes Risk Behaviors in India: A Prospective, Parallel Group Cohort Study

Abstract: BackgroundIn low/middle income countries like India, diabetes is prevalent and health care access limited. Most adults have a mobile phone, creating potential for mHealth interventions to improve public health. To examine the feasibility and initial evidence of effectiveness of mDiabetes, a text messaging program to improve diabetes risk behaviors, a global nonprofit organization (Arogya World) implemented mDiabetes among one million Indian adults.ObjectiveA prospective, parallel cohort design was applied to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 19 publications
2
85
0
Order By: Relevance
“…Studies from India have shown mHealth is feasible and improves health outcomes in subjects with diabetes. Text messaging improved health behavior related to diabetes [8]. Similarly, a pilot study of mHealth intervention was compared to usual care in three metropolitan cities across India over a 6-month period [9].…”
mentioning
confidence: 99%
“…Studies from India have shown mHealth is feasible and improves health outcomes in subjects with diabetes. Text messaging improved health behavior related to diabetes [8]. Similarly, a pilot study of mHealth intervention was compared to usual care in three metropolitan cities across India over a 6-month period [9].…”
mentioning
confidence: 99%
“…The majority of the identified interventions had no theoretical basis, and most of them used traditional methods of education such as individual/group counseling or printed material, and most did not achieve a significant change in dietary behaviour [4045,48]. Whilst a few studies have reported change in one or another dietary behaviour using information technology tools most had one of the methodological flaws mentioned above [40,49,50,51]. Moreover, most interventions to date have been developed and evaluated in developed countries, except a few previous studies in India [4951].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst a few studies have reported change in one or another dietary behaviour using information technology tools most had one of the methodological flaws mentioned above [40,49,50,51]. Moreover, most interventions to date have been developed and evaluated in developed countries, except a few previous studies in India [4951]. The effectiveness of interventions based on information technology has not been established as yet.…”
Section: Discussionmentioning
confidence: 99%
“…Pfammatter et al 14 also used mHealth procedure to motivate the participants to follow a healthy lifestyle. In both the studies participants were also contacted through personal reviews or through telephonic interview.…”
Section: Discussionmentioning
confidence: 99%